2012
DOI: 10.1002/ptr.4842
|View full text |Cite
|
Sign up to set email alerts
|

Gingerol‐Induced Hypoxia‐Inducible Factor 1 Alpha Inhibits Human Prion Peptide‐Mediated Neurotoxicity

Abstract: Prion diseases are a family member of neurodegenerative disorders caused by the accumulation of misfolded-prion proteins (scrapie form of PrP, PrP(Sc)). The accumulation of PrP(Sc) in the brain leads to neurotoxicity by the induction of mitochondrial-apoptotic pathways. Recent studies implicated gingerol in protection against neurodegeneration. However, the basis of the neuroprotection in prion disease remains unclear. Thus, we investigated the influence of gingerol on prion peptide-induced neuronal damage. Gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…The compound was also found to block prion peptide-mediated neurotoxicity by protecting mitochondrial function, which is associated with the expression of hypoxia-inducible factor 1a (Jeong et al, 2013). 6-Gingerol and SG were predicted in silico to be strong antidepressants, using Argus lab 4.0.1 docking software, when compared to the standard drug, imipramine (Ittiyavirah and Paul, 2013).…”
Section: Activity On the Central Nervous Systemmentioning
confidence: 99%
“…The compound was also found to block prion peptide-mediated neurotoxicity by protecting mitochondrial function, which is associated with the expression of hypoxia-inducible factor 1a (Jeong et al, 2013). 6-Gingerol and SG were predicted in silico to be strong antidepressants, using Argus lab 4.0.1 docking software, when compared to the standard drug, imipramine (Ittiyavirah and Paul, 2013).…”
Section: Activity On the Central Nervous Systemmentioning
confidence: 99%
“…It has been shown that hypoxia regulates β-catenin activation through the modulation of HIF-1α stabilization (26,31) and that HIF-1α protects neuronal cells against PrP (106-126)induced mitochondrial damage (11). Therefore, in this study, we assessed whether HIF-1α has an effect on PrP (106-126)-mediated mitochondrial toxicity by activating β-catenin signals.…”
Section: Neuroprotective Effects Of Hif-1α Against Prion-induced Neurmentioning
confidence: 96%
“…effects of HIF-1α are associated with the regulation of mitochondrial functions (11,35). In this study, we demonstrate that HIF-1α prevents prion-mediated mitochondrial neurotoxicity by regulating β-catenin signaling pathways.…”
mentioning
confidence: 88%
See 2 more Smart Citations